Lipid accumulation product: a powerful marker of metabolic syndrome in healthy population - Taverna, Mariano Javier (2011)
Objective: The metabolic syndrome (MS) is a cluster of cardiometabolic factors which predisposes to diabetes and cardiovascular disease (CVD). Early detection of high-risk individuals for MS using accurate measures of insulin resistance (IR) could improve detection and prevention of CVD and diabetes. The aim of this study was to explore the ability of LAP (lipid accumulation product), compared to traditional measures of IR, to identify MS. Design: 768 Spanish adults were recruited. MS was assessed using the revised criteria of NCEP/ATP III (National Cholesterol Education Program/Adult Treatment Panel III) and IDF (International Diabetes Federation). Measures of IR such as HOMA-IR and LAP, an index of lipid accumulation based on a combination of waist circumference and serum triglycerides, were calculated. ROC analysis was performed in order to detect the parameter with the best predictive capability for MS. Results: The prevalence of MS-NCEP/ATPIII and MS-IDF was 15.1 and 20.5% for men, respectively, and 15.4 and 17.5% for women. LAP showed the highest diagnostic accuracy for MS-NCEP/ATPIII (AUC 0.91 and 0.90 among males and females) and MS-IDF (0.88 for both males and females). This was confirmed by internal validation using 20,000 bootstrap samples. Among males and females, different LAP cutoff values exhibited high sensitivity (78-85%) and specificity (78-81%) for MS-NCEP/ATPIII and MS-IDF prediction with elevated efficiency (proportion of positives and negatives classified correctly by the test = 78-85%). Conclusions: LAP has a strong and reliable diagnostic accuracy for MS-IDF and, especially, MS-NCEP/ATPIII among nondiabetic adult females and, in particular, among males from Spain.